Note on Lieb-Thirring Type Inequalities for a Complex Perturbation of Fractional Laplacian - Dubuisson, C. (Журнал математической физики, анализа, геометрии, 2015)
For s > 0, let H0 = (-∆)s be the fractional Laplacian. In this paper, we obtain Lieb-Thirring type inequalities for the fractional Schrödinger operator defined as H = H0 + V , where V ∈ Lp(ℝd), p ≥ 1, d ≥ 1, is a complex-valued potential. Our methods are based on the results of articles by Borichev-Golinskii-Kupin [BGK09] and Hansmann [Han11] Для s > 0 пусть H0 = (-∆)s будет дробным лапласианом. В данной статье мы получаем неравенства типа Либа-Тирринга для дробного оператора Шредингера, который определяется как H = H0 + V, где V ∈ Lp(ℝd), p ≥ 1, d ≥ 1, - комплексный потенциал. Наши методы основываются на результатах работ Borichev-Golinskii-Kupin (Bull. Lond. Math. Soc. 41 (2009), No. 1, 117-123) и Hansmann (Lett. Math. Phys. 98 (2011), No. 1, 79-95).